2011
DOI: 10.1042/bst0390195
|View full text |Cite
|
Sign up to set email alerts
|

The catalytic mechanism of Pseudomonas aeruginosa cd1 nitrite reductase

Abstract: The cd1 NiRs (nitrite reductases) are enzymes catalysing the reduction of nitrite to NO (nitric oxide) in the bacterial energy conversion denitrification process. These enzymes contain two distinct redox centres: one covalently bound c-haem, which is reduced by external electron donors, and another peculiar porphyrin, the d1-haem (3,8-dioxo-17-acrylate-porphyrindione), where nitrite is reduced to NO. In the present paper, we summarize the most recent results on the mechanism of nitrite reduction by the cd1 NiR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 51 publications
0
14
0
Order By: Relevance
“…This reactivity is similar to the reaction of nitrite with Hb, Mb and Ngb (17, 33) and the bacterial nitrite reductase (34) in which a coupled electron and proton transfer to nitrite to generate NO. Recent report by Sturms et al (29) showed that hemoglobin from cyanobacterium Synechocystis and class 1 rice non-symbiotic Hb are also able to convert nitrite to NO under anoxic conditions and our work extends their findings.…”
Section: Discussionmentioning
confidence: 61%
“…This reactivity is similar to the reaction of nitrite with Hb, Mb and Ngb (17, 33) and the bacterial nitrite reductase (34) in which a coupled electron and proton transfer to nitrite to generate NO. Recent report by Sturms et al (29) showed that hemoglobin from cyanobacterium Synechocystis and class 1 rice non-symbiotic Hb are also able to convert nitrite to NO under anoxic conditions and our work extends their findings.…”
Section: Discussionmentioning
confidence: 61%
“…1B). 5 Further reduction of nitric oxide generates nitrous oxide, 6 which is eventually reduced further to dinitrogen. 7,8 Thus, CcNiR reduces nitrite to NH 4 + without releasing any intermediate, and Cd 1 NiR reduces nitrite to release NO.…”
Section: Introductionmentioning
confidence: 99%
“…With two protons from the distal residues, a molecule of water is released, forming a {FeNO} 6 intermediate (Enemark-Feltham notation). 5,9,10 The CcNiR avoids the formation of the dead-end intermediate, {FeNO} 7 through two consecutive proton-coupled electron transfer (PCET) to the {FeNO} 6 species, generating an {FeHNO} 8 intermediate, 11 which, on further reduction, leads to the generation of NH 4 + . 9 Alternatively, Cd 1 NiR forms {FeNO} 7 through an electron transfer (ET) from cytochrome c, and releases NO with the concomitant binding of nitrite to the ferrous heme-d 1 and the cycle continues.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Chen & Strous [93] have suggested the possibility that rather than from NO, O 2 and N 2 may be produced from N 2 O. We would like to note that the examples of enzymes transforming both O 2 and NO, such as the O 2 /NO-reductase superfamily [94] or cd 1 -nitrite reductase (cd 1 -Nir) [95] suggest the possibility rstb.royalsocietypublishing.org Phil Trans R Soc B 368: 20120258 of NO itself substituting for O 2 in the methane-to-methanol conversion via CH 4 þ 2NO , CH 3 OH þ N 2 O (as indicated by the arrow next to the question mark in the left-hand side scheme of figure 3). For the case of the O 2 /NO-reductase superfamily, it has indeed been proposed, based on phylogenetic evidence, that the NO-converting enzyme pre-dates in evolutionary terms the O 2 -reducing one [44].…”
mentioning
confidence: 96%